Philippines’ Fluidity of Innovation from 2001 to 2021: Interpretations and Implications - Jose, David S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
While innovation is generally accepted as one of the drivers of economic growth, most innovation metrics are qualitative and have a relatively lesser impact on policymaking than their quantitative counterparts. With this challenge, this paper presents another quantitative metric: the Fluidity of Innovation applied in the Philippines from 2001 to 2021. The study analyses data from public government reports and reputable private entities using the contextualized Reynolds Number from fluid mechanics. The findings reveal a significant transformation in the Philippines' innovation, moving from a laminar (smooth and predictable) to a turbulent (rapid and complex) phase; this indicates the country has a growing capacity to cater to rapid development in technology such as Artificial Intelligence and Quantum Computers. Since the Philippines is leaning towards a turbulent flow of innovation, some technology will be felt as Radical Innovation instead of Disruptive Innovation across the industries that allow the labor force to experience empowerment rather than a complete layoff. This research contributes to the broader understanding of innovation's role in the Philippine economy and fiscal policies, particularly those for innovation and technology.